2020
DOI: 10.48550/arxiv.2012.00392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A semi-analytical treatment to wind accretion in neutron star supergiant high mass X-ray binaries: I. eccentric orbits

E. Bozzo,
L. Ducci,
M. Falanga

Abstract: We present in this paper a first step toward a semi-analytical treatment of the accretion process in wind-fed neutron star supergiant X-ray binaries with eccentric orbits. We consider the case of a spherically symmetric wind for the supergiant star and a simplified model for the accretion onto the compact object. A self-consistent calculation of the photoionization of the stellar wind by the X-rays from the accreting neutron star is included. This effect is convolved with the modulation of the mass accretion r… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…This breathing mode induces a subsequent modulation of the mass accretion rate onto the neutron star, with ∼30 minutes long offstates during which the accretion is quenched, separated by a characteristic duration in reasonable agreement with a characteristic time scale of the X-ray emission from Vela X-1 reported in Kreykenbohm et al (2008). Recently, Bozzo et al (2020) designed a detailed semi-analytical model of a smooth spherically symmetric wind and showed that accounting for the eccentricity of the orbit leads, for a simplified model of accretion, to an average mass accretion rate almost 3 times higher near periastron than near apoastron. Due to the accretion wake interception the line-of-sight at orbital phases 0.4-0.8, precisely when the neutron star is near apoastron, it is difficult to disentangle between a drop of the intrinsic emission and an increase of the absorption, even using hard X-rays observations.…”
Section: Variability Of the Mass Accretion Ratesupporting
confidence: 81%
“…This breathing mode induces a subsequent modulation of the mass accretion rate onto the neutron star, with ∼30 minutes long offstates during which the accretion is quenched, separated by a characteristic duration in reasonable agreement with a characteristic time scale of the X-ray emission from Vela X-1 reported in Kreykenbohm et al (2008). Recently, Bozzo et al (2020) designed a detailed semi-analytical model of a smooth spherically symmetric wind and showed that accounting for the eccentricity of the orbit leads, for a simplified model of accretion, to an average mass accretion rate almost 3 times higher near periastron than near apoastron. Due to the accretion wake interception the line-of-sight at orbital phases 0.4-0.8, precisely when the neutron star is near apoastron, it is difficult to disentangle between a drop of the intrinsic emission and an increase of the absorption, even using hard X-rays observations.…”
Section: Variability Of the Mass Accretion Ratesupporting
confidence: 81%